E-120 Relationship of cerebral autoregulation via pressure reactivity index and delayed cerebral ischemia in aneurysmal subarachnoid hemorrhage. (23rd July 2022) - Dowlati, E; Keating, G; Felbaum, D; Mai, J; Chang, J
Abstract : Background: Patients with aneurysmal subarachnoid hemorrhage (SAH) continues to have poor functional outcome due to occurrence of delayed cerebral ischemia (DCI). Although vasospasm represent the primary therapeutic target for mitigating DCI, DCI largely occurs through multifocal etiologies that include cerebral dysautoregulation. Higher pressure reactivity indexes (PRx) which consists of a moving correlation coefficient between intracranial pressures and mean arterial pressures have been shown in isolated case reports to be associated with DCI. Clinical Presentation: Two patients presented with high-grade SAH and comatose exams. However, patient one, a SAH from a ruptured right middle cerebral artery, continued having intact PRx values (average value of -0.07 during hospital days 9–19), while having severe, refractory vasospasm that required intra-arterial verapamil and angioplasty. At the conclusion of his hospitalization, patient one was functionally independent, had negligible DCI, and was discharged to home. Patient two, SAH from a ruptured anterior communicating artery, had an improving PRx ranging from -0.1 to 0.1. However, upon developing severe vasospasm, her PRx increased to the 0.2–0.6 range (overall PRx from hospital days 4–16 was 0.3), and she suffered from extensive DCI in both middle cerebral and anterior cerebral artery distributions and ultimately progressed to brain death from her malignant cerebral edema. The figure demonstrates PRx vs. Ttme (days) for patients with SAH and vasospasm. Conclusion: Cerebral autoregulation as measured by PRx may represent a viable target and prove helpful for neuroprognostication by evaluating whether patients with SAH develop DCI after suffering from severe vasospasm. Further studies evaluating the role of cerebral autoregulation and PRx and its pathophysiological role in DCI are warranted. Disclosures: E. Dowlati: None. G. Keating: None. D. Felbaum: None. J. Mai: None. J. Chang: None.